Degradasi Lapisan Cat Pelindung Korosi Pada Plat Lambung Kapal Terhadap Aliran Air Laut, Air Tawar, dan Air Payau - Lilik budiyanto; Yulianto Yulianto (Politeknik Ilmu Pelayaran Semarang, 2022)
Indonesia is a country consisting of islands and oceans. The existence of ships as a means of sea transportation plays an important role in connecting between regions separated by the ocean in human distribution and logistics needs. Part of the ships that often suffers damage due to operational and corrosive environments is the hull. One of the protections for the hull is paint coating. As a protector on the ship the paint layer is thinning due to friction with water media which can cause damage to the paint layer and reduce the protection function of the ship's hull plate from corrosion. This study aims to determine the effect of the flow of seawater, fresh water and brackish water on the hull paint. This research uses an experimental method, with the experimental variables were three types of paint which are applied to the steel plate remaining from the ship's hull installation. In this study, a comparison of the paint layer was calculated before and after the specimen placement process on water variable media for 7 days with a constant flow rate. The results of this study indicate that seawater media has the highest level of depletion in the hull paint layer.